Changes in treatment patterns for patients with locally advanced rectal cancer in the United States over the past decade: An analysis from the National Cancer Data Base. Issue 13 (13th April 2016) - Sineshaw, Helmneh M.; Jemal, Ahmedin; Thomas, Charles R.; Mitin, Timur
Abstract : BACKGROUND: In the United States, neoadjuvant chemoradiotherapy (NACRT) is widely accepted as the standard of care in the treatment of patients with locally advanced rectal cancer. In the current study, the authors attempted to examine patterns of treatment in the United States over the past decade. METHODS: Using the National Cancer Data Base, a total of 66, 197 patients who were diagnosed with American Joint Committee on Cancer stage II to III rectal adenocarcinoma and treated between 2004 and 2012 were identified. The authors described trends in the receipt of treatment for 3 time periods (2004‐2006, 2007‐2009, and 2010‐2012) and analyzed 5‐year overall survival probabilities for 28, 550 patients treated between 2004 and 2007. RESULTS: Receipt of NACRT increased significantly from 42.9% between 2004 and 2006 to 50.0% between 2007 and 2009, and to 55.0% between 2010 and 2012 ( P < .0001). In contrast, the use of adjuvant chemoradiotherapy (CRT) decreased from 16.7% between 2004 and 2006 to 10.5% between 2007 and 2009, and to 6.7% between 2010 and 2012 ( P < .0001). Similarly, the use of surgery alone decreased from 13.1% between 2004 and 2006 to 8.7% between 2010 and 2012 ( P < .0001). Older age, the presence of comorbidities, larger primary tumor size, lymph node involvement, not being of non‐Hispanic white race/ethnicity, lack of private insurance, and treatment at a facility that did not have a high case volume were associated with a significantly lower possibility of receiving NACRT. The 5‐year overall survival rates for patients treated with NACRT, surgery and adjuvant CRT, surgery alone, and definitive CRT were 72.4%, 70.9%, 44.9%, and 48.8%, respectively. CONCLUSIONS: The use of NACRT before surgery in US patients with rectal cancer has substantially increased over the past decade. However, only approximately one‐half of patients currently receive this standard therapy, which could be explained in part by socioeconomic factors. Trimodality therapy is associated with the best outcomes for these patients. Cancer 2016;122:1996–2003 . © 2016 American Cancer Society . Abstract : Analysis of the National Cancer Data Base revealed that over the past decade, the adoption of neoadjuvant chemoradiotherapy has been increasing in the United States for patients with locally advanced rectal cancer. Unfortunately, only approximately one‐half of US patients currently receive the standard care with trimodality therapy, which is in part related to socioeconomic factors.